2021
DOI: 10.1371/journal.pone.0254929
|View full text |Cite
|
Sign up to set email alerts
|

Norcycloartocarpin targets Akt and suppresses Akt-dependent survival and epithelial-mesenchymal transition in lung cancer cells

Abstract: In searching for novel targeted therapeutic agents for lung cancer treatment, norcycloartocarpin from Artocarpus gomezianus was reported in this study to promisingly interacted with Akt and exerted the apoptosis induction and epithelial-to-mesenchymal transition suppression. Selective cytotoxic profile of norcycloartocarpin was evidenced with approximately 2-fold higher IC50 in normal dermal papilla cells (DPCs) compared with human lung cancer A549, H460, H23, and H292 cells. We found that norcycloartocarpin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 95 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…A polyphenol compound, PE5, efficiently suppresses Akt/mTOR, and Bcl-2 induces autophagic cell death in NSCLC [ 47 ]. Norcycloartocarpin targeting Akt suppresses cancer cell motility by suppressing the epithelial-mesenchymal transition [ 48 ]. Recently, the inhibitor of Akt was shown to have a potential for cancer stem cell inhibition [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A polyphenol compound, PE5, efficiently suppresses Akt/mTOR, and Bcl-2 induces autophagic cell death in NSCLC [ 47 ]. Norcycloartocarpin targeting Akt suppresses cancer cell motility by suppressing the epithelial-mesenchymal transition [ 48 ]. Recently, the inhibitor of Akt was shown to have a potential for cancer stem cell inhibition [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that compounds isolated from Artocarpus gomezianus , the Thai medicinal plant, have promising antimetastatic activity in human lung cancer cells [ 32 , 33 , 34 ]. Here, we have revealed novel information about the effect of the new active compound, cycloartocarpin ( Figure 1 A), extracted from A. gomezianus , on EMT and cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Formins are responsible for the linear polymerisation of F-actin in filopodia while fascin cross-links the formed filaments in parallel bundles [ 68 , 69 ]. Formation of filopodia [ 70 , 71 ] downstream of activation of TWIST1 and SNAIL1 [ 72 ] and the expression of formins [ 73 , 74 ] regulate the migration of cancer cells undergoing EMT. Additionally, the upregulation of formins contributes to metastasis formation [ 75 ], and high levels of fascin correlate with poor prognosis in a number of cancers including breast, lung, gastrointestinal and oral squamous cell carcinoma [ 64 , 76 , 77 ], suggesting that their role in EMT contributes to cell invasion and the formation of secondary tumour foci.…”
Section: Invasive Adhesions Formed By Cells Undergoing Emt In Solid T...mentioning
confidence: 99%